Trump and American Fascism. Issue 4 (2nd October 2017) - Harris, Jerry; Davidson, Carl; Fletcher, Bill; Harris, Paul
ABSTRACT: The election of Donald Trump reflects the rise of a Right-wing nationalist movement. Central to Trump's appeal has been his advocacy of anti-immigrant, racist, and misogynist ideas. At its core, his ruling power bloc consists of neo-liberal fundamentalists, the religious Right, and white nationalists. There are similarities between the new power bloc and fascism, and there are many who see Trump's administration as such. Nevertheless, the new president's authoritarian power bloc is neither hegemonic nor fascist, but such a definition can send oppositional strategy in the wrong direction.